Verification on policies for network functions in SDN/NFV-based environment - Haoyu CHEN; Deqing ZOU; Hai JIN (网络与信息安全学报)
Although the newly introduced SDN and NFV technologies bring flexibility and convenience in network management, the dynamic forwarding policies introduced by SDN may cause invalidation in the network function policies, and the policies in different network functions may also cause conflicts due to their own behaviors.In order to verify the policies in SDN/NFV-based cloud network, the verification on policies between the network function and the SDN device, as well as across the network functions were considered.A unified policy expression for analysis was summarized, and policy verification scheme, framework and prototype implementation were proposed to verify the correctness of polices in different scenarios, then experiments were conducted to justify the effectiveness and performance